Application of α-amylase as a novel biodemulsifier for destabilizing amphiphilic polymer-flooding produced liquid treatment. (July 2018) - Jiang, Jiatong; Wu, Hairong; Lu, Yao; Ma, Tao; Li, Zhe; Xu, Derong; Kang, Wanli; Bai, Baojun
Highlights: A novel environmental friendly biodemulsifier α-amylase is proposed. α-Amylase is a highly efficient biodemulsifier at room temperature. The de-emulsification mechanism of α-amylase is explored by various methods. Abstract: The performance and de-emulsification mechanism of α-amylase, a novel environmental friendly biodemulsifier in petroleum industry, was investigated at room temperature. The effects of α-amylase on the viscosity of amphiphilic polymer solution and de-emulsification rate were studied by changing the concentration of α-amylase, temperature and salinity. Polymer molecular weight, Zeta potential, interfacial film strength and interfacial tension were measured to investigate the de-emulsification mechanism of α-amylase. The results show that α-amylase is an efficient biodemulsifier to increase the de-emulsification rate of amphiphilic polymer emulsions. Hydrolysis of α-amylase to amphiphilic polymers destroys the structure of the amphiphilic polymer, thereby reduces the viscosity and the interfacial film strength of the system. Once de-emulsification is completed, the lower layer, i.e. the emulsified layer, will be clear. Thus, α-amylase can be applied as an effective de-emulsifier for amphiphilic polymer-stabilized O/W emulsion.